Differences in fat distribution between metabolically unhealthy people with normal weight versus obesity, NHANES 2011–2018 - Rajesh Garg; Seerat Anand; Tejasvi Pasupneti; Youngju Pak; Sreevastav Teja Kalangi (BMJ Open Diabetes Research & Care)
Introduction Metabolic abnormalities are present in 15–25% of adults with body mass index (BMI)<25 kg/m2. While previous studies have shown that metabolically unhealthy individuals with lean body weight (MUL) and metabolically unhealthy individuals with obesity (MUO) exhibit increased visceral adiposity, direct comparisons between these groups have not been performed. Differences between the two groups may suggest different mechanisms of metabolic disease and may affect treatment strategies.Research design and methods We used the National Health and Nutrition Examination Survey data (2011–2018) that included dual energy X-ray absorptiometry. Metabolic dysfunction was defined as the presence of ≥2 components of the metabolic syndrome, excluding obesity. The differences in body fat distribution between unhealthy and healthy individuals were studied with an interaction term to evaluate whether the effect of BMI differs by the metabolic health status.Results We found that both MUL and MUO groups had increased android to gynoid fat ratio as compared with metabolically healthy groups with normal or lean weight (MHL) and metabolically healthy with obesity (MHO), respectively. Total fat and android fat were higher in MUL as compared with MHL individuals, in men as well as in women. Gynoid fat was higher in MUL men but not in women. However, MUO individuals had similar total fat but lower gynoid fat as compared with MHO individuals, in men as well as in women. Android fat was significantly higher in the male MUO group but not in the female MUO group.Conclusions The study shows increased android fat as the main abnormality in MUL individuals and decreased gynoid fat as the main abnormality in MUO individuals. The differences in android and gynoid fat patterns between MUL and MUO groups suggest different mechanisms of metabolic dysfunction in people who are lean versus those with obesity.